The creative PhD : challenges, opportunities, reflection - Brabazon, Tara; Lyndall-Knight, Tiffany; Hills, Natalie (Emerald Publishing Limited, 2020)
Doctorates awarded based on artefact and exegeses, and enabled through creative-led research, are a minority enrolment which suffer from wildly diverse examination expectations and assumptions about quality. Widening the disciplinary parameters and currency of this kind of doctorate, The Creative PhD is the first book that challenges the standards, structure and value of this research. The authors, themselves leading authorities on doctoral education, break fresh ground by demonstrating that rather than being intrinsically wedded to the creative arts or media studies, arts-based research practice doctorates can transcend traditional humanities subjects, becoming instead a model of organizing knowledge, developing methodologies and presenting research. Offering a critical reflection on the contemporary state of the PhD, the authors probe and reshape creative-led research to increase transparency for doctoral students, supervisors and examiners, inviting readers to access a new pathway to how original research is created, supervised and assessed.
Keywords: Doctor of philosophy degree.; Education, Adult & Continuing Education.; Adult education, continuous learning.; elektronické knihy; electronic books